Exploring The Message of Environmental Awareness and Collective Action in The Movie - Veronika, Imelda; Marta, Rustono Farady; Dong, Liang; Rifandi, Teguh; Yanti, Yanti; Agustina, Anna (Institut Seni Indonesia Yogyakarta, 2025)
The animated film “Wall-E”, produced by Pixar, is not only for entertainment purposes, but also conveys important messages about environmental issues and the crisis of our planet. The aim of this study is to examine environmental messages in the movie “Wall-E” with the help of Critical Discourse Analysis. The method used is Critical Discourse Analysis, which was developed by Norman Fairclough. The criticism in this film study is intended to describe human behavior that has an impact on the environment. The theory on which this study is based is Robert Cox's Environmental Communication Theory. In this study, the interaction between visual, aural and narrative elements in the film is examined and these elements contribute to the formation of meaning and awareness of the environmental crisis. The results of the analysis show that “Wall-E” effectively conveys themes such as pollution, overconsumption and human indifference to the planet. In addition, the film is also socially critical of modern consumer culture and emphasizes the importance of dialogue and participation in sustainability efforts. It is expected that this study will provide new insights into the role of media in raising environmental awareness and encouraging collective action to overcome the existing crisis.